Logistic contribution from the vision of the technical services in the hotel industry - Roberto Torres-Rodríguez; Rodobaldo Martínez-Vivar; Alexander Sánchez-Rodríguez; Reyner Pérez-Campdesu\~ner; Gelmar García-Vidal (Journal of Industrial Engineering and Management (JIEM), 2019)
Purpose: The aim of this paper is based on the theoretical and empirical analysis, with the application of multivariate statistics, for the identification of the essential variables that intervene in the technical services processes of the hotel industry and with it the conformation of a theoretical model for the management of this process. Design/methodology/approach: The methodology designed, used for the processing of research, consists of three phases of development where the selection of variables that from the theoretical order appear in the literature consulted, which are subject to comprehensive to an analysis of experts to confirm its existence in the object of practical study. Subsequently, the design of the evaluation methods of the selected variables is carried out, culminating with the analysis of relationships and influences between variables. All of the above under the multivariate statistics approach. Findings: The main results of this research are achieved after the systematic application of the methodology designed, observing the existence of three essential perspectives that affect the management of technical services in hotel industries, which contain a total of 35 variables which were corroborated from the multivariate statistics. These results allowed the creation of a theoretical model for the management of this process, contributing from the logistical approach with the integration of this subsystem to the business management of the hotel sector. Originality/value: The literature shows multiple theoretical sources referring to studies on technical services in productive entities, observing limitations to address this issue from the order of services and with greater emphasis for the cases of the hotel industries. The originality of this material lies in the experimental identification of the main limitations explicit and (or) implicit in contemporary theory, to address the process of technical services in the hotel industry. From the contributions made as part of this investigation, it is possible to identify those incident variables in this process and their grouping into three perspectives. This result illustrates the performance of this process based on the theoretical model proposed.
Keywords: 650; Logistic; technical services; hotel industry; environmental perspective; social perspective; technological perspective